A Prospective and Comparative Study on the Efficacy of The Escitalopram and Citalopram in Major Depressive Disorder Patients - Anton Vinoth, T (International Journal of Pharmaceutical & Biological Archive, 2014)
A Prospective and Comparative Study on the Efficacy of The Escitalopram and Citalopram in Major Depressive Disorder Patients